Computational Thinking for Primary School Teachers: Building Problem-Solving and Literacy Skills - Maria Teodora Ping; Yuni Utami Asih; Ida Wardani (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Problem-solving is one of the skills that is crucial to equip students to face a variety of challenges in the future as well as related to the development of their lifelong literacy skills. One of the potential solutions for promoting students’ problem-solving skills is introducing Computational Thinking. However, in the context of schools in East Kalimantan, both teachers and students have not been familiar with Computational Thinking. Therefore, this current pilot study aimed at introducing Computational Thinking to teachers, especially primary school teachers, by developing a workshop and a module suitable to the local contexts and needs. This study involved 22 primary school teachers from Kutai Kartanegara Regency who had no prior knowledge and experience concerning Computational Thinking. The teachers were trained the basic concepts of CT and how to implement CT in the class especially in relation to literacy aspects. Afterwards, the teachers were assigned to develop a CT-infused lesson and did a self-reflection on the process. The findings from the post-workshop questionnaires indicated that most teachers showed positive attitudes towards CT and implementing CT in their lessons. Furthermore, they also voiced out that they would like to learn further about CT, particularly related to Literacy and the Minimum Competency Assessment (AKM).